Production and Investment Response to Changing Market Conditions, Technical Know-How, and Government Policies: A Vintage Model of the Agricultural Sector - Cigno, Alessandro (Review of Economic Studies, 1971)
Journal Article Production and Investment Response to Changing Market Conditions, Technical Know-How, and Government Policies: A Vintage Model of the Agricultural Sector Get access Alessandro Cigno Alessandro Cigno University of Birmingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 1, January 1971, Pages 63–94, https://doi.org/10.2307/2296623 Published: 01 January 1971